QAWAID TAFSIR : THE APPLICATION OF SYNTAX, MORPHOLOGY, AND RHETORIC BY M. QURAISH SHIHAB (B. 1944) - Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi; Azwar, Azwar (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2024)
M. Quraish Shihab (Shihab) is one of the great exegetes in the Indonesian archipelago. He is well known for applying QawÄâ€˜id al-TafsÄ«r in interpreting the Quran. These rules are popular among many exegetes to support their interpretations aligned with the teachings and goals of the Quran. Furthermore, to ensure the interpretations do not deviate from the valid message of the Quran. This paper adopts an analytical approach in Tafsir Al-Mishbah to describe the Syntax, Morphology, and Rhetoric of selected Quranic verses. It shows that QawÄ'id al-TafsÄ«r is an essential tool in Quranic exegesis. Mastering these rules can help interpret certain verses that have similar meanings. This paper also proves that Shihab had adopted QawÄâ€˜id al-TafsÄ«r that earlier exegetes used.